Reutilização de requisitos em linhas de processos de negócio - Sorgatto, Doglas W.; Paiva, Débora M. B.; Cagnin, Maria Istela (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2019: Anais do XV Simpósio Brasileiro de Sistemas de Informação, 2019)
The cost reduction in the Requirement Engineering process finds in business process modeling a way of aligning business goals with software requirements, and for development companies that have development demands in the same domain, greater savings can be found with the adoption of Business Process Lines (BPL). From this perspective, this paper presents the ARReq, which is an approach that allows the elicitation, specification and reuse of requirements from BPLs. It has been defined to provide quality attributes, suggested by ISO/IEC 29.148, to the functional, non-functional requirements and business rules elicited with the support of any elicitation technique applicable to BPMN business process models. A qualitative analysis was carried out and allowed to observe that ARReq is scalable, has low coupling with BPLs management approaches, besides specifying the requirements reused in the formats of user stories and requirements document and to provide a traceability matrix to support the software maintainability